Property rights as a public policy tool: an empirical analysis of the social and economic effects - Moura, Mauricio José Serpa Barros de (2009)
Secure property rights are considered a key determinant of economic development. However, the evaluation of the causal effects of land titling is a di¢ cult task. The Brazilian government through a program called ‘Papel Passado’ has issued titles, since 2004, to over 85,000 families and has the goal to reach 750,000. This thesis examines the direct impact of securing a property title on income, labor supply, happiness and child labor force participation. In order to isolate the causal role of ownership security, this study uses a comparison between two close and very similar communities in the City of Osasco (a town with 654,000 people in the S„o Paulo metropolitan area). The key point of this case is that some units get the program and others do not. One of them, Jardim Canaã was chosen to receive the titles in 2007, but the other, Jardim DR, given fiscal constraints, only will be part of the program schedule in 2012, and for that reason became the control group in this research. In terms of Public Policy response to economic growth, understand the effect on income is relevant to measure the ‘Papel Passado’ developmental impact. Furthermore, another topic in Public Policy, that is crucial for developing economies, is child labor force participation. Particularly, in Brazil, about 5.4 million children and teenagers between 5 and 17 years old are still working full time. Last, but not least, how could such subject be related with happiness? The economics of happiness has been applied to a range of issues. These include the relationship between income and happiness, inequality and poverty, the effects of macro-policies on individual welfare and the effect of institutional conditions such as democracy, federalism and security. An evaluation of happiness as a causal effect of land titling has never been applied and such thesis intends to provide an additional input regarding this topic. The estimates suggest, using basically the Difference-in-Difference (DD) econometric approach, that titling results in increase of income and decrease of child labor hours. Also, applying ordered probit model, the property rights have positive impact on happiness as well. Hence, the thesis has presented new evidence on the value of formal property rights in urban squatter community in a developing country.